Mechanisms of Pine Disease Susceptibility Under Experimental Climate Change - Ghosh, Soumya K.; Slot, Jason C.; Visser, Erik A.; Naidoo, Sanushka; Sovic, Michael G.; Conrad, Anna O.; Kyre, Bethany; Vijayakumar, Vinod; Bonello, Pierluigi (Frontiers in Forests and Global Change, 2022)
Climate change (CC) conditions projected for many temperate areas of the world, expressed by way of excessive temperatures and low water availability, will impact forest health directly by means of abiotic stress but also by predisposing trees to pathogenic attack. However, we do not yet know how such environmental conditions alter the physiology and metabolism of trees to render them more susceptible to pathogens. To explore these mechanisms, we conditioned 2-3-year-old Austrian pine saplings to a simulated CC environment (combined drought and elevated temperatures), followed by pathogenic inoculation with two sister fungal species characterized by contrasting aggressiveness, Diplodia sapinea (aggressive) and D. scrobiculata (less aggressive). Lesion lengths resulting from infection were measured after three weeks to determine phenotypes, while dual transcriptomics analysis was conducted on tissues collected from the margins of developing lesions on separate branches 72 hours post inoculation. As expected, CC conditions enhanced host susceptibility to the less aggressive pathogen, D. scrobiculata, to a level that was not statistically different from the more aggressive D. sapinea. Under controlled climate conditions, D. sapinea induced suppression of critical pathways associated with host nitrogen and carbon metabolism, while enhancing its own carbon assimilation. This was accompanied by suppression of host defense-associated pathways. In contrast, D. scrobiculata infection induced host nitrogen and fatty acid metabolism as well as host defense response. The CC treatment, on the other hand, was associated with suppression of critical host carbon and nitrogen metabolic pathways, alongside defense associated pathways, in response to either pathogen. We propose a new working model integrating concurrent host and pathogen responses, connecting the weakened host phenotype under CC treatment with specific metabolic compartments. Our results contribute to a richer understanding of the mechanisms underlying the oft-observed increased susceptibility to fungal infection in trees under conditions of low water availability and open new areas of investigation to further integrate our knowledge in this critical aspect of tree physiology and ecology.